Mechanism and kinetics of combustion-carbothermal synthesis of AlN nanopowders. Issue 12 (15th August 2017) - He, Qing; Qin, Mingli; Huang, Min; Chu, Aimin; Lu, Huifeng; Chen, Pengqi; Wang, Hao; Qu, Xuanhui
Abstract: In this work, the carbothermal reduction-nitridation process of low-temperature combustion synthesis (LCS) (Al2 O3 +C) precursor was investigated in detail. Compared with conventional precursor, the LCS precursor possesses many advantages such as amorphous structure, nanosized particles, homogeneous mixing at molecular level. The experimental results indicate that the methods for preparing precursor exert great influence on phase transformation of Al2 O3, onset temperature of nitridation and reaction activity. During the calcination, the phase transformation of Al2 O3 is hindered by a large amount of surrounding C particles rendering Al2 O3 maintains high reactivity. Accordingly, the nitridation reaction initiates at 1300 °C and completes at 1500 °C for 2 h. Furthermore, the reaction mechanism was also discussed on the basis of experiments. More significantly, it is established that the activation energy of carbothermal reduction-nitridation reaction using LCS precursor is Eα=336 KJ/mol.